Navigating alcohol’s impact: A mixed-methods analysis of community perceptions and consequences in Northern Tanzania - Alena Pauley; Madeline Metcalf; Mia Buono; Kirstin West; Sharla Rent; William Nkenguye; Yvonne Sawe; Mariana Mikindo; Joseph Kilasara; Bariki Mchome; Blandina T. Mmbaga; João Ricardo Nickenig Vissoci; et al. (PLoS ONE, 2025)
Background Worldwide, alcohol is a leading risk factor for death and disability. Tanzania has particularly high rates of consumption and few resources dedicated to minimizing alcohol-related harm. Ongoing policy efforts are hampered by dynamic sociocultural, economic, and regulatory factors contributing to alcohol consumption. Through the voices of Kilimanjaro Christian Medical Centre (KCMC) patients, this study aimed to investigate community perceptions surrounding alcohol and the impact of its use in this region. Methods This mixed-methods study was conducted at KCMC between October 2021 and May 2022. 676 adult (≥18 years old) Kiswahili-speaking patients who presented to KCMC’s Emergency Department (ED) or Reproductive Health Clinic (RHC) were enrolled through systematic random sampling to participate in quantitative surveys. Nineteen participants were selected for in-depth interviews (IDIs) through purposeful sampling. The impact and perceptions of alcohol use were measured through Drinkers’ Inventory of Consequences (DrInC) scores and analyzed in RStudio using means and standard deviations. IDI responses were explored through a grounded theory approach using both inductive and deductive coding methodologies in NVivo. Results Men attending the ED were found to have the highest average [SD] DrInC scores (16.4 [19.6]), followed by ED women (9.11 [13.1]), and RHC women patients (5.47 [9.33]), with higher scores indicating a broader array of consequences. Participants noted alcohol to have both perceived advantages and clear harms within their community. Increased conflict, long-term health outcomes, financial instability, stigma, and sexual assault were seen as negative consequences. Benefits were primarily identified for men and included upholding cultural practices, economic growth, and social unity. Physical and financial harm from alcohol impacted both genders; however, alcohol-related stigma and sexual assault were found to affect women disproportionately. Conclusion Our findings suggest that perceptions around drinking are nuanced, and alcohol’s social and physical consequences differ significantly by gender. To effectively minimize local alcohol-related harm, future alcohol-focused research and policy efforts should consider the complex sociocultural role that alcohol holds in the Moshi community.